URGENSI DAN RELEVANSI PENDIDIKAN MODERASI BERAGAMA DALAM PENDIDIKAN AGAMA DI SEKOLAH - Ari Benawa (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2021)
ABSTRACTReligion from the perspective of understanding and from the historical point of view, its emergence has the nuances of peace and harmony for life in this world and for the eternal life. However, in its development, religion which has a positive meaning has been manipulated by individuals and groups for power and economic interests and other interests that are not in harmony with the moral values of religion itself. Because of these, the excesses of religion emerged, such as ritualism, fanaticism, radicalism, and intolerant attitudes between religious communities. All of them have extreme nuances. There are extreme in terms of ritual, that is ritualism; extreme in their own beliefs, that is fanaticism; extreme in their implementation, that is radicalism which is anti-contextualization of religious teachings and laws. Another extreme of such religiosity is skepticism and even contra-religion which give birth to a secularistic attitude. These two extremes certainly contradicted with the values of Pancasila which are the basic and ideology of the Indonesian nation and state. It is the concern that triggered this study to offer moderate religious education as the bridge between the two extremes in religion which the Ministry of Religion in Indonesia calls religious moderation. With a phenomenological study and literature review, this article is packaged to achieve this goal. So, from the study of the problem with its religious theories, the conclusion is that in the context of Indonesia, which is plural in terms of religion as well as ethnicity and race, it cannot be other than that religious moderation education urgent to be instilled in students from the early age, because it is very relevant now and in the future for the nation and the unitary state of the Republic of Indonesia to remain firmly standing in line with the sacred motto: Bhineka Tunggal Ika. Keywords: Religious moderation, religion, religious education, Pancasila